2014
DOI: 10.1096/fj.13-246108
|View full text |Cite
|
Sign up to set email alerts
|

FOXL2 transcriptionally repressesSf1expression by antagonizing WT1 during ovarian development in mice

Abstract: Steroidogenic factor 1 (SF1; Ad4BP/NR5A1) plays key roles in gonadal development. Initially, the Sf1 gene is expressed in mouse fetal gonads of both sexes, but later is up-regulated in testes and down-regulated in ovaries. While Sf1 expression is activated and maintained by Wilms tumor 1 (WT1) and LIM homeobox 9 (LHX9), the mechanism of sex-specific regulation remains unclear. We hypothesized that Sf1 is repressed by the transcription factor Forkhead box L2 (FOXL2) during ovarian development. In an in vitro sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Wt1 vivo -morpholino treatment, initiated at the same developmental stage also revealed specific effects of WT1 in embryonic ovaries as exemplified by the reduction of Dax1 and Foxl2 mRNA levels (Fig 4B). It has recently been reported that FOXL2 antagonizes the stimulatory effect of WT1(-KTS) on Nr5a1 expression by interacting with the proximal Nr5a1 promoter region [47]. Our data provide evidence that WT1 also interferes with the transcriptional network controlling ovarian development.…”
Section: Discussionsupporting
confidence: 56%
“…Wt1 vivo -morpholino treatment, initiated at the same developmental stage also revealed specific effects of WT1 in embryonic ovaries as exemplified by the reduction of Dax1 and Foxl2 mRNA levels (Fig 4B). It has recently been reported that FOXL2 antagonizes the stimulatory effect of WT1(-KTS) on Nr5a1 expression by interacting with the proximal Nr5a1 promoter region [47]. Our data provide evidence that WT1 also interferes with the transcriptional network controlling ovarian development.…”
Section: Discussionsupporting
confidence: 56%
“…It has been reported that Sf1 is required for the development of steroidogenic cells and that loss of Sf1 results in agenesis of gonads and adrenal glands (Luo et al, 1994;Sadovsky et al, 1995). The relationship between Wt1 and Sf1 has been studied previously using TM3 (Takasawa et al, 2014), TM4 (Wilhelm and Englert, 2002) and C2C12 (Val et al, 2007) cell lines. These results suggest that the expression of Sf1 was activated by WT1.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in ovarian phenotypes between human patients and mutation-induced mice may reflect the inter-species differences in the expression pattern of NR5A1/Nr5a1 in immature ovaries. Nr5A1 transcripts are barely detectable in the murine ovary during the critical period for gonadal formation, whereas NR5A1 mRNA is continuously expressed in the human fetal ovary [4, 11]. It has been suggested that in the human fetal ovary, NR5A1 activates several anti-testis genes, such as CTNNB and WNT4 [5], and antagonizes nuclear receptor subfamily 0 group B member 1 (NR0B1) to suppress SOX9 expression [4, 6].…”
Section: Discussionmentioning
confidence: 99%